The Diary: Autobiographical Writing in its Sociocultural Dimension, Cognitive and Creative Possibilities (2017)
Diary writing is immerse in the personal and social life of our culture as a tool for social analysis and a personal writing exercise. This reflection article presents and describes examples of diary writing in different contexts, ranging from artistic creation to educational processes, pointing out the potentialities of autobiographical writing for the subjective, cognitive and creative spaces of individuals.